Providing better services to all through the implementation of e-governance at the local government level in South Africa - Mokgopo, T. I. (International Conference on Public Administration and Development Alternatives, 2018)
The sphere of local government in South Africa is often viewed as an institution that is closest to people. It is also perceived to be the first point of contact between members of community and government institutions. This means that most service delivery objectives that are contained in the Constitution of the Republic of South Africa are achieved at the local government level, thereby making municipalities the most important institution in the country. This saw municipalities being able to touch any area or communities where the national and provincial government cannot reach including disadvantage rural areas. Such development led to the introduction of e-governance as a way of providing services to both public and private sector in the country. The main reason is that the internet has become an important way to conduct business and to communicate between government departments and members of the community. However, current evidence points to the fact that local governments worldwide, including South Africa, have been slow to respond to these developments: the implementation of e-governance and use of internet to provide e-services. Based on that this paper advocates for the implementation of e-governance at the local government level in South Africa as a measure of improving and achieving Constitutional objectives of providing better services for all. This paper argues that through e-government or e-governance, municipalities will be in a better position to respond to service delivery challenges faced by members of the community because in itself (e-governance) public participation is achievable. The paper concludes that local e-governance is a better way of providing municipal services to different communities in the country. Keywords: E-governance, E-government, Good governance, Implementation, Information technology, Local government
Article published in: The 3rd Annual International Conference on Public Administration and Development Alternatives 04 - 06 July 2018, Stellenbosch University, Saldahna Bay, South Africa
Keywords: E-government; Good governance; Information technology; Local government; Public welfare.; Public administration